Involvement of aph(3′)-IIa in the formation of mosaic aminoglycoside resistance genes in natural environments - Woegerbauer, Markus; Kuffner, Melanie; Domingues, Sara; Nielsen, Kaare M. (Frontiers in Microbiology, 2015)
Intragenic recombination leading to mosaic gene formation is known to alter resistance profiles for particular genes and bacterial species. Few studies have examined to what extent aminoglycoside resistance genes undergo intragenic recombination. We screened the GenBank database for mosaic gene formation in homologs of the aph(3’)-IIa (nptII) gene. APH(3’)-IIa inactivates important aminoglycoside antibiotics. The gene is widely used as a selectable marker in biotechnology and enters the environment via laboratory discharges and the release of transgenic organisms. Such releases may provide opportunities for recombination in competent environmental bacteria. The retrieved GenBank sequences were grouped in 3 datasets comprising river water samples, duck pathogens and full-length variants from various bacterial genomes and plasmids. Analysis for recombination in these datasets was performed with the Recombination Detection Program, RDP4, and the Genetic Algorithm for Recombination Detection, GARD. From a total of 89 homologous sequences, 83% showed 99% - 100% sequence identity with aph(3’)-IIa originally described as part of transposon Tn5. Fifty one were unique sequence variants eligible for recombination analysis. Only a single recombination event was identified with high confidence and indicated the involvement of aph(3’)-IIa in the formation of a mosaic gene located on a plasmid of environmental origin in the multi-resistant isolate Pseudomonas aeruginosa PA96. The available data suggest that aph(3’)-IIa is not an archetypical mosaic gene as the divergence between the described sequence variants and the number of detectable recombination events is low. This is in contrast to the numerous mosaic alleles reported for certain penicillin or tetracycline resistance determinants.